Correction: A fluorescent aptasensor for ATP based on functional DNAzyme/walker and terminal deoxynucleotidyl transferase-assisted formation of DNA-AgNCs. Issue 6 (22nd February 2023) - Cai, Shixin; Chen, Xin; Chen, Haohan; Zhang, Yuting; Wang, Xiaoli; Zhou, Nandi
Abstract : Correction for 'A fluorescent aptasensor for ATP based on functional DNAzyme/walker and terminal deoxynucleotidyl transferase-assisted formation of DNA-AgNCs' by Shixin Cai et al., Analyst, 2023, 148, 799–805, ; https://doi.org/10.1039/D2AN02006H .